Análise das ferramentas de implementação e manutenção da certificação ISO 14001 - Rodrigues, Lucas Azevedo (Universidade Federal de São Carlos, 2023)
The objective of this work is to identify the main motivations, benefits and difficulties in the certification of adoption of Environmental Management Systems ISO 14001 in Brazilian companies. The use of Environmental Management Systems – EMS based on ISO 14001 has proved to be a fundamental tool for approaching the environmental aspects and impacts of an organization. Despite all the benefits that this system provides, many difficulties are faced for the implementation of EMS, especially in small and medium-sized companies - SMEs. The main implementation problems related to ISO 14001 or the models and methods used (PIM) were pointed out, highlighting the lack of environmental performance criteria, the need for a path or sequence of steps for implementation, the cooperation of employees in the compliance and commitment to the implementation of this standard. After the implementation of the certification, the problems do not end, it is challenging to maintain the mandatory parameters over time. The main benefits obtained were: improvement of quality in processes and greater awareness of employees in relation to quality.
Analysis of implementation tools and maintenance of ISO 14001 certification
Keywords: Sistema de gestão ambiental; ISO 14001; Fatores críticos; Environmental management system; Critical factors; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL::CONTROLE DA POLUICAO; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS